Graphene and the Immune System: A Romance of Many Dimensions - Mukherjee, Sourav P.; Bottini, Massimo; Fadeel, Bengt (Frontiers in Immunology, 2017)
Graphene-based materials (GBMs) are emerging as attractive materials for biomedical applications. Understanding how these materials are perceived by and interact with the immune system is of fundamental importance. Phagocytosis is a major mechanism deployed by the immune system to remove pathogens, particles, and cellular debris. Here we discuss recent studies on the interactions of GBMs with different phagocytic cells, including macrophages, neutrophils, and dendritic cells. The importance of assessing GBMs for endotoxin contamination is discussed as this may skew results. We also explore the role of the bio-corona for material interactions with immune cells. Finally, we highlight recent evidence for direct plasma membrane interactions of GBMs.